Japan [videorecording] - The Travel Preview System (Houston, Tex. Travelview International, 1996)
Features the traditions and culture of Japan, the land of the rising sun.
Title on container: Japan : the beginning of a great vacation.
VHS.
Keywords: Japan -- Description and travel